ВОЗНИКНОВЕНИЕ КОНСУЛЬСКОГО ИНСТИТУТА (Journal of actual problems of jurisprudence, 2019)
The conclusion of the capitulation was justified by the fact that in Muslim countriesno legislation or judicial or Executive authority was provided at the time of signingcapitulation of sufficient guarantees for nationals of European States in respect of personalsecurity and property. The capitulation regime was based on consular jurisdiction, inaccording to which the European Consul had jurisdiction over all the Affairs of their compatriots, andalso those in which one of the parties was a citizen of the Eastern state. ForeignEuropean citizens who were under the jurisdiction of his Consul, did not obey the localauthorities.